Mediating the nation-building agenda in public service broadcasting: convergence active user-generated content (AUGC) for television in Kenya - Ambala, Anthony Terah (My University, 2016)
The  violence,  destruction  and  death  of  more  than  1  200  people  resulting  from   the  highly  disputed  2007  election  results  in  Kenya  was  a  considerable  watershed   moment.  It  exposed  the  deep  fragmentation  within  the  nation-‐state  and  became   a  significant  fissure  for  the  simmering  tensions  among  the  42  “tribes”  of  Kenya.   In  the  media-‐scape,  these  events  evinced  the  elitist  and  tribal  hegemony  in  media   ownership  and  revealed,  more  than  ever  before,  that  certain  voices  and   narratives  were  privileged  over  others.  These  events  also  unmasked  recurrent   motifs,  which  illuminated  the  stranglehold  that  the  political,  media  and  economic   elites  wielded  over  media  instruments  and  platforms,  for  their  own  benefit.       This  study  aims  to  explore  the  extent  to  which  active  user-‐generated  content  in   the  digital  media  space  can  intervene  in,  and  disrupt,  some  of  these  exclusionary   practices  in  the  public  service  mediascape,  to  potentially  inspire  a  re-‐imagination   in  this  space  for  nation  building  in  Kenya.  It  is  premised  on  a  participatory  action   research  approach  that  draws  on  theoretical  discourse  on  nationalism  and   nation  building,  as  this  is  the  field  from  which  the  study’s  key  problems  stem  and   where  conceptual  discourses  on  digital  media  converge.  The  study  also  draws  on   participatory  discourses  in  the  media,  as  these  potentially  present  an   emancipatory  platform  for  those  on  the  margins  of  the  hegemonic  centres.  Here   it  mainly  draws  on  Bhabha’s  cultural  difference  theory,  Billig’s  banal   nationalisms,  Jenkins’  ideas  on  convergence  culture,  Carpentier’s  thoughts  on   maximalist  media  participation  and  Thumim’s  assertions  on  self-‐representation   in  the  digital  space.     The  study  also  hinges  on  the  practice-‐informed  pilot  project  titled  Utaifa   Mashinani  Masimulizi  ya  Ukenya  (UMMU)  digital  narratives,  co-‐created  by  the   researcher  together  with  the  Abakuria  (the  Kuria  people)  of  Kenya.  This  is  a   community  marginally  represented  in  the  public  service  broadcasting-‐scape  in   Kenya  and  a  people  whose  narrative  discourse  is  seldom  present  in  the  public   sphere.     The  study  argues  that  broadcast  content  –  not  just  in  Kenya  but  also  in  Africa  –   on  User  Generated  Content  (UGC)  for  broadcasting  predominantly  focuses  on   passive  forms  of  UGC  rather  than  Active  User  Generated  Content  (AUGC)  -‐  a  term   coined  in  this  study  to  refer  to  user-‐generated  content  that  entails  a  more   meaningful,  emancipatory  and  empowering  form  of  participation  amongst  those   traditionally  referred  to  as  consumers  of  broadcast  content.  It  contends  that   although  many  contemporary  television  broadcasters  around  the  world  continue   to  create  a  perception  of  increasing  and  robust  audience  participation  in   televised  content,  in  Kenya  this  is  certainly  not  the  case.  It  argues  that  significant   forms  of  current  participation  on  television  are  illusionary,  minimalist  and  futile,   as  they  largely  entrench  television’s  balance  of  power  among  the  media  elites.   Ordinary  people  are  often  ‘invited’  to  participate  in  broadcasting,  but  their  entry   point  into  these  narratives  tends  to  be  limited  to  accessing  already-‐completed   narratives  and  engaging  in  what  constitutes  token  participation,  with  minimal,   and  in  most  cases,  no  impact  on  the  story,  its  conception,  distribution  and  socio-‐ economic  benefits.       Drawing  on  insights  from  the  UMMU  project,  the  study  proposes  that  AUGC  can   potentially  disrupt  some  of  the  existing  tropes  and  motifs  in  the  Public  Service   Mediascape  opening  up  spaces  for  multiple  and  diverse  voices  and  narratives  in   Kenya.  This  potentially  enables  active  participation  from  constituencies  that   have  traditionally  been  on  the  margins  of  the  Kenyan  nation-‐state  to  partake  in   the  nation  building  process.
A thesis submitted to the Faculty of Humanities, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2016
Keywords: South African Broadcasting Corporation; Public broadcasting--Kenya; Television broadcasting--Kenya